Chemical evolution for taming the 'pathogenic kinase' PAK1. Issue 6 (June 2020) - Maruta, Hiroshi; Kittaka, Atsushi
Highlights: PAK1 is the major 'pathogenic' kinase. Several potent PAK1 blockers developed are introduced for treatment of a wide variety of PAK1-dependent diseases including cancers and pandemic COVID-19 infection. Abstract : To celebrate the 25th anniversary of the cloning of the first mammalian p21-activated kinases (PAKs) (RAC/CDC42-activated kinases) by Ed Manser, the first international PAK symposium was held in NYC in October 2019. Among six distinct PAKs in mammals, PAK1 is the major 'pathogenic kinase', the abnormal activation of which is responsible for a wide variety of diseases and disorders including cancers, ageing processes and infectious and inflammatory diseases such as pandemic coronaviral infection. Recently, for a clinical application, a few potent (highly cell-permeable and water-soluble) PAK1 blockers have been developed from natural or synthetic PAK1 blockers (triptolide, vitamin D3 and ketorolac) via a series of 'chemical evolutions' that boost pharmacological activities >500 times.